La investigación en la empresa familiar: un debate sobre la existencia de un campo independiente - J. T. Basco Rodrigo (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
In the nineties, the family-owned firm made room for new trends in research, and managed to break fresh grounds as a field of study within Business Management. The scepticism created by the existence of a possible intellectual field has raised a debate on the family-owned enterprise, which could be either considered as an independent field or else, as an extension of the vision of the firm developed by the existing theories in the various fields of study. It is from this idea that this article deals in depth with the intrinsic and extrinsic elements that can be approached to reflect on the study of the family-owned company as a brand-new domain. Conclusions show some important taken steps, as regards the extrinsic elements, towards an independent approach on the generation of ideas when their evolution is compared to other fields of knowledge. Nevertheless, there is a long way to walk in relation to the building of theories. This path is to be covered with the interested parties and with the help of investigation that focus on innovations related to the elements that affect the development of family-owned firms, and which may consolidate a comprehensive knowledge without fragmented visions.
Keywords: 330; family-owned company; field; efficiency